Lycopene, a carotenoid, attenuates cyclosporine-induced renal dysfunction and oxidative stress in rats - Atessahin, Ahmet; Ceribasi, Ali Osman; Yilmaz, Seval (Wiley, 2007)
The aim of this study was to investigate the possible protective role of antioxidant treatment with lycopene on cyclosporine A-induced nephrotoxicity using biochemical and histopatological approaches. Adult male Sprague-Dawley rats were randomly divided into four groups. The control group received physiological saline; animals in the lycopene group received only lycopene (10 mg/kg); animals in the cyclosporine A group received only cyclosporine A (15 mg/kg) and animals in cyclosporine plus lycopene group received cyclosporine and lycopene for 21 days. The effects of lycopene on cyclosporine A-induced nephrotoxicity were evaluated by plasma creatinine, urea, sodium and calcium concentrations; kidney tissue thiobarbituric acid reactive species, reduced glutathione (GSH), glutathione peroxidase (GSH-Px) and catalase activities and histopatological examinations. Administration of cyclosporine A to rats induced a marked renal failure, characterized with a significant increase in plasma creatinine and urea concentrations. Cyclosporine A also induced oxidative stress as indicated by increased kidney tissue concentrations of thiobarbituric acid reactive species and GSH, and reduced activities of GSH-Px and catalase. Moreover, the kidneys of cyclosporine A-treated rats showed tubular necrosis, degeneration, dilatation, thickened basement membranes, luminal cast formation and inter-tubular fibrosis. Lycopene markedly reduced elevated plasma creatinine, urea levels and counteracted the deleterious effects of cyclosporine A on oxidative stress markers. In addition, lycopene ameliorated cyclosporine A-induced pathological changes including tubular necrosis, degeneration, thickened basement membranes and inter-tubular fibrosis when compared to the alone cyclosporine A group. These data indicate that the natural antioxidant lycopene might have protective effect against cyclosporine-induced nephrotoxicity and oxidative stress in rat.
Keywords: Induced Nephrotoxicity; Lipid-Peroxidation; Supplementation; Metabolism; Toxicity; Oxygen; Model; Acid